Rooting potential of ilex paraguariensis cuttings of two populations of southern Brazil in two rooting environments - Nascimento B.* (2022)
© 2022The success of Ilex paraguariensis cutting can be affected by the population of origin, as well as the genotype and the rooting environment. Therefore, the objective of this search was to test the vegetative propagation of I. paraguariensis cuttings from two populations and their genotypes inserted in two rooting environments. The populations tested were from Três Barras (TB) and Urupema (UR), both from Santa Catarina state, by selecting seven genotypes in each. After collecting and cutting, the populations and genotypes were evenly distributed in two rooting environments, one being a mini tunnel (MT) with irrigation by micro sprinklers and the other in a greenhouse with intermittent nebulization (GWIN) with temperature and humidity control. Survival was considerably low for both populations but with singular results, as TB was better adapted to GWIN (36.5%) and UR to MT (22.6%). The rooting of cuttings varied greatly in all perspectives. The TB population obtained the best rooting results inside GWIN (21.7%), while UR did not achieve 5% of rooting in MT (2.4%) nor in GWIN (3.2%). The genotypes TB6, TB3 and TB1 obtained the best rooting results for TB in GWIN (all above 30.0%), while only UR3 obtained significant results in GWIN (18.8%). These results, mainly regarding survival and rooting, confirm that there is a strong relation involving the origin place of the material, the individuals of a population and the rooting environments.